KOMUNIKASI KEBANGSAAN DALAM EKOSISTEM MEDIA DIGITAL - Taufik, Cevi M; Pertiwi, R Dewi (JURNAL KEBANGSAAN RI, 2024)
The noble history of the nation is tarnished because the communication system deviates from the nature and identity. For some citizens, the values ​​of politeness, mutual respect and tolerance as the basic glue of the nation are no longer considered relevant. Changes occurred and soon changed the paradigm of national and state life as a consequence of intense interaction with foreign cultures. Even culture itself is considered traditional so it is not very appropriate to apply it in the context of a very modern era. The essence of nationality as a basic value is starting to be replaced by new values ​​that are being formed and refer to global values. Adab and politeness as part of national communication have faded. Nationality, as the main source of values ​​for all citizens of the nation, must be the main reference in conveying various matters relating to communication. However, in this era, we face very tough challenges. Based on these conditions, this research aims to determine the application and influence of changes in national values ​​in communication practices that occur in online media networks. To explain this further, the method used is a qualitative method which aims to explain the background that is the object behind the visible symptoms. The research results show that communication will have national value if it is carried out by referring to values, norms and ethics that originate from the nation's treasures.